Pengembangan Sistem Informasi Perpustakaan Universitas Sepuluh Nopember Papua Dengan Metode Air Terjun - Astrin Aprilia Umasugi; Astika Ramadhani; Emy L.Tatuhey; Umasugi, Astrin Aprilia; Ramadhani, Astika; Tatuhey , Emy Lenora (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to design and develop a web-based Library Information System at the Sepuluh Nopember University of Papua to support the digitalization of library services in a more efficient and integrated manner. The development method used is the Waterfall model, with a UML-based modeling approach that includes Use Case, Activity, and Class Diagrams. The system is equipped with various features such as book and member management, QR Code-based borrowing and returning, statistical dashboards, automatic report printing, and password encryption using bcrypt to ensure data security. Testing was conducted using the Black-box Testing method to validate that all core functionalities operate as required, and performance testing was performed using Apache JMeter to measure system response time. The results indicate that the system runs stably, with response times within the normal range. However, there are still some limitations, including the absence of an implemented audit log for user activity tracking and the lack of full-scale testing in a production environment. Therefore, this system is expected to serve as an adaptive digital solution in supporting modern library services, especially in Eastern Indonesia.